Proceso atención de enfermería en lactante mayor con gastroenteritis. - Gavilanes Lara, Eliana Katherine (2022)
Gastroenteritis is inflammation of the gastrointestinal tract, in the pediatric age may have its origin in: viruses such as rotavirus (most common etiologic agent of acute gastroenteritis in children) adenoviruses, enteroviruses, astroviruses, caliciviruses. Bacteria: salmonella, campylobacter, parasites: giardia lamblia. The most frequent symptoms are diarrhea in the increase of stools of lesser consistency, accompanied by fever, vomiting and colic abdominal pain. The present case study was carried out based on an older infant with gastroenteritis, in the pediatric area of the Alfredo Noboa Montenegro General Hospital in the City of Guaranda, Province of Bolívar, Period May 2021- April 2022. The older infant presented nausea accompanied by vomiting after admission, in moderate amount of food content led to thermal rise, not quantified and abdominal pain of mild intensity that is radiated to the hypogastrium. The hospitalization time of the older infant was four days, a factor that allowed an adequate follow-up to evaluate the productivity of the nursing care process, especially those focused on aspects related to prophylaxis, prevention, execution of Nursing care.